2020
DOI: 10.1017/s1755773920000247
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing professionals? How the democratic and professionalized nature of interest groups shapes their degree of access to EU officials

Abstract: Interest groups are key intermediary actors between civil society and public officials. The EU has long emphasized the importance of interacting with representative groups that involve their members. Additionally, there is an increasing trend toward the professionalization of groups that invest in organizational capacities to efficiently provide policy expertise. Both member involvement and organizational capacity are crucial features for groups to function as transmission belts that aggregate and transfer the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 64 publications
1
35
0
2
Order By: Relevance
“…In relation to earlier research on professionalization and the tension created when interest organizations develop business-like strategies (Sanders and McClellan 2014;Kreutzer and Jäger 2011), this article emphasizes the tension between strategic decisions connected to role orientations that may have consequences for the democratic development, and for the CSO's potential contribution to civic engagement. The functional differentiation (Albareda 2020) and professionalization of civil society, understood as employing more experts (Salamon 1999), could perhaps enhance the organizations' advocacy performance, and it does not necessarily have to decrease members' involvement and internal democracy (Heylen et al 2020). This article, however, points specifically toward the importance of the types of policy professionals taking office within CSOs.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In relation to earlier research on professionalization and the tension created when interest organizations develop business-like strategies (Sanders and McClellan 2014;Kreutzer and Jäger 2011), this article emphasizes the tension between strategic decisions connected to role orientations that may have consequences for the democratic development, and for the CSO's potential contribution to civic engagement. The functional differentiation (Albareda 2020) and professionalization of civil society, understood as employing more experts (Salamon 1999), could perhaps enhance the organizations' advocacy performance, and it does not necessarily have to decrease members' involvement and internal democracy (Heylen et al 2020). This article, however, points specifically toward the importance of the types of policy professionals taking office within CSOs.…”
Section: Discussionmentioning
confidence: 95%
“…Not all types of policy professionals were interviewed across all organizations. However, judging by the organizations' web pages, all organizations in the selection can be characterized by high organizational capacity, meaning that they are skilled in generating policy expertise and a high level of access to decision-makers (see Albareda 2020).…”
Section: Methodology and Case Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quest for success-in form of access-may oppose an interest group's inclination to assure legitimacy through reflexivity. Some scholars postulate that the biggest obstacle of achieving legitimate representation is the credo for effectiveness and with it, an increased professionalisation of interest groups (Albareda 2020;Maloney 2012Maloney , 2015Halpin 2006Halpin , 2010. This indicates a potential tradeoff between reflexivity and thus enhanced legitimacy on the one hand, and professionalisation and access on the other.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to transmission belt practice, many studies have shown a trend among groups towards professionalization characterized by elite-level (staff and leadership) dominated decision-making and less membership participation and involvement (Albareda 2020;Jordan and Maloney 1998;Halpin 2006Halpin , 2010Klüver and Saurugger 2013;Maloney 2015). As noted by van Deth and Maloney (2012, p. 2): 'From the beginnings of the 1980s we see a gradual organizational change.…”
Section: Introductionmentioning
confidence: 98%